Indonesian Diaspora's Preferences for Dual Citizenship: Opportunities and Challenges for National Resilience - Chris Setio Wardoyo; Adrianus Eliasta Melialas; Muhammad Alvi Syahrin (Jurnal Indonesia Sosial Teknologi, 2025)
The Indonesian diaspora, which is spread across various parts of the world, has great potential to support national development through remittances, investment, technology transfer, and strengthening nation branding. However, Indonesia's single citizenship policy creates a dilemma for the diaspora, forcing them to choose between Indonesian citizenship or the country of residence. This study aims to identify diaspora preferences for dual citizenship policies, analyze emerging opportunities and challenges, and develop recommendations for implementation strategies for this policy. The results of the study show that the dual citizenship policy can increase diaspora involvement in national development, strengthen economic stability, and support Indonesia's public diplomacy. However, the implementation of this policy requires mitigating risks such as double loyalty and legal conflicts through comprehensive regulatory design. With the right policies, the diaspora can become a strategic asset to support national resilience and the vision of Golden Indonesia 2045.